Pengaruh Media Lagu Anak-Anak Berbahasa Arab Dalam Meningkatkan Keterampilan Istima’ Siswa Di Lamongan: Pengaruh Media Lagu Anak-Anak Berbahasa Arab Dalam Meningkatkan Keterampilan Istima’ Siswa Di Lamongan - lili musyafa'ah; luthfi aziz (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2022)
Research on the influence of Arabic children's song media in improving the special abilities of 4th grade students of SD Muhammadiyah Lamongan has a background problem, namely 4th grade students of SD Muhammadiyah Lamongan consider Arabic difficult and there are Arabic songs by the school. teachers exist but are not very effective in improving students' special abilities. This study aims to determine the difference after and before using children's song media. The method used is quantitative involving 30 students. Collecting data using observation methods, questionnaires, questionnaires, and tests. The results of the one sample test t-test calculation show a significance value of 0.000 <0.05. So it can be said that the Arabic song media has an effect on the special abilities of 4th grade students of SD Muhammadiyah Lamongan